Morphological study of Superabsorbent polymer hydrogels from sago starch - Omar, Nurizan; Ahmad, Zuraida; Nordin, Norhuda Hidayah (Trans Tech Publications, Switzerland, 2012)
This paper comprises of the characterizations of superabsorbent polymer hydrogels based on sago starch (SS) prepared via graft copolymerization method with acrylic acid (AA) in the presence of ammonium persulphate (APS) and N, N-metylenebisacrylamide. The morphology of sago-g-acrylic (SAG) was evidenced by scanning electron microscope (SEM) images. The remarkable feature of this SAG is the porosity distribution with different amount of crosslinker. Less amount of crosslinker leads to increment in porosity distribution as well as water absorbency. This SAG with excellent water absorbency properties, being biodegradable in nature could be useful in sanitary products, horticulture and agriculture.